2018
DOI: 10.3991/ijet.v13i02.8085
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Promoters of and Barriers to Use of a Learning Management System in an Undergraduate Nursing Program

Abstract: Abstract-Effective presentation of information is essential in teaching and learning. We assessed the promoters of and barriers to utilization of a learning management system, namely Blackboard ! (Blackboard Inc., Washington DC, USA), by undergraduate nursing students. We investigated their utilization of Blackboard ! and provided recommendations to improve their teaching and learning. We conducted a cross-sectional survey of 304 women in their second to fourth years of study using a validated questionnaire th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Much of the research to date has focused on LMS features that influence student satisfaction, including a perceived inability to communicate efficiently with staff and other students through the LMS (Al-Drees et al., 2015; Alhosban and Ismaile, 2018; Damnjanovic et al., 2015; Kuo and Belland, 2016; Paechter and Maier, 2010). Other research has shown that, although students like the convenience of online learning (Heirdsfield et al., 2011), they are generally not happy with the amount and quality of interaction with staff and peers within the online learning environment (Cole et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research to date has focused on LMS features that influence student satisfaction, including a perceived inability to communicate efficiently with staff and other students through the LMS (Al-Drees et al., 2015; Alhosban and Ismaile, 2018; Damnjanovic et al., 2015; Kuo and Belland, 2016; Paechter and Maier, 2010). Other research has shown that, although students like the convenience of online learning (Heirdsfield et al., 2011), they are generally not happy with the amount and quality of interaction with staff and peers within the online learning environment (Cole et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Moyle, 2010) Learning management systems (LMS) and online learning are interconnected. Consequently, every distant university is crafting its learning management system (LMS) and making it accessible with convenience for distant learners to get their education from remote & manageable areas (Alhosban, &Ismaile, 2018).…”
Section: __________________________________________________________________________mentioning
confidence: 99%
“…Wherein, n is the number of courses evaluated; l is the serial number of objects participating in the evaluation; 0 ( ) l Ixyz  refers to the correlation coefficient of the lth object participating in the evaluation on the attribute of the Ixyzth index. This study gives the data processing results of the third-level index "degree of teaching resource level meeting teaching demand" 21 ( 1,2) I Z Z  in 2019, namely, the calculation results of correlation coefficient matrix F21Z, as shown in Table 4. The data processing of other third-level indexes is omitted here.…”
Section: Application Of Four-in-one Teaching Mode Integrated With Ucd Theory In Nursing Coursementioning
confidence: 99%
“…How to accelerate the cultivation of nursing personnel who adapt to the society, market, industry and future is a topic to be solved urgently by nursing education workers and managers. Fundamental Nursing covers basic nursing theory, elementary knowledge and skills which must be mastered by clinical nursing workers, and it is the foundation for learning specific nursing and also the core course of nursing personnel training [2]. Thus, teaching reform of this course is a focus of relevant educators.…”
Section: Introductionmentioning
confidence: 99%